Brain functional connectivity differentiates dexmedetomidine from propofol and natural sleep. (28th September 2017) - Guldenmund, P.; Vanhaudenhuyse, A.; Sanders, R. D.; Sleigh, J.; Bruno, M. A.; Demertzi, A.; Bahri, M. A.; Jaquet, O.; Sanfilippo, J.; Baquero, K.; Boly, M.; Brichant, J. F.; et al.
Abstract: Background: We used functional connectivity measures from brain resting state functional magnetic resonance imaging to identify human neural correlates of sedation with dexmedetomidine or propofol and their similarities with natural sleep. Methods: Connectivity within the resting state networks that are proposed to sustain consciousness generation was compared between deep non-rapid-eye-movement (N3) sleep, dexmedetomidine sedation, and propofol sedation in volunteers who became unresponsive to verbal command. A newly acquired dexmedetomidine dataset was compared with our previously published propofol and N3 sleep datasets. Results: In all three unresponsive states (dexmedetomidine sedation, propofol sedation, and N3 sleep), within-network functional connectivity, including thalamic functional connectivity in the higher-order (default mode, executive control, and salience) networks, was significantly reduced as compared with the wake state. Thalamic functional connectivity was not reduced for unresponsive states within lower-order (auditory, sensorimotor, and visual) networks. Voxel-wise statistical comparisons between the different unresponsive states revealed that thalamic functional connectivity with the medial prefrontal/anterior cingulate cortex and with the mesopontine area was reduced least during dexmedetomidine-induced unresponsiveness and most during propofol-induced unresponsiveness. The reduction seen during N3 sleep was intermediate between those of dexmedetomidine and propofol. Conclusions: Thalamic connectivity with key nodes of arousal and saliency detection networks was relatively preserved during N3 sleep and dexmedetomidine-induced unresponsiveness as compared to propofol. These network effects may explain the rapid recovery of oriented responsiveness to external stimulation seen under dexmedetomidine sedation. Trial registry number: Committee number: 'Comité d'Ethique Hospitalo-Facultaire Universitaire de Liège' (707); EudraCT number: 2012-003562-40; internal reference: 20121/135; accepted on August 31, 2012; Chair: Prof G. Rorive. As it was considered a phase I clinical trial, this protocol does not appear on the EudraCT public website.